A review of policy documents on Early Childhood Care and Education of Bangladesh and Nepal for comparative analysis of their policies and interventions strategies - Hossain Miah, M.Tofazzel (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2011.